L'élaboration et le fonctionnement des mécanismes d'arbitrage au sein de I'ALE et de FALENA, du GATT et de l'OMC - Bastien, Frédéric (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1995)
The increasing importance of international trade explains in great part the role that dispute resolution plays in trade agreement. Diversification, government's intervention in the economy, readiness of interest groups to defend their cause, all these elements make trade negotiations a much more difficult task today thon it used to be fifty years ago. Quarrels and dispute over international trade are therefore more likely to arise and it's impossible today to negotiate international trade agreements without dispute resolution mecanism. Success or failure of different type of arbitration lies in the definition of the substantive rules of trade agreements. For binding arbitration to work properly, such rules must be clear and precise. But this solution implies that independant countries renounce in part to their sovereignty. To do so, Canada and the United States decided to keep their own trade laws and accepted to submit them to binding arbitration. The same thing was done when free trade was extended to Mexico. At multilateral level, this type of arrangement would be much more difficult to implement.